Study for Operation Method of Underwater Cable and Pipeline Burying ROV Trencher using Barge and Its Application in Real Construction - Min-Gyu Kim (한국해양공학회지, 2020)
We developed a heavy-duty work class ROV trencher named URI-T (Underwater robot it’s trencher) that can conduct burial and maintenance tasks for underwater cables and small diameter pipelines. It requires various supporting systems, including a dynamic positioning (DP) vessel, launch and recovery system (LARS), A-frame, and winch in order to perform burial tasks because of its dimensions (6.5 m × 5.0 m × 4.5 m, 20 t) and the tough working environment. However, operating a DP vessel has disadvantages as it is expensive to rent and operate and it is difficult to adjust the working schedule for some domestic coast construction cases. In this paper, we propose a method using a barge instead of a DP vessel to avoid the above disadvantages. Although burying the cable and pipeline using a barge has lower working efficiency than a DP vessel, it can save construction expenses and does not require a large crew. The proposed method was applied over two months at the construction of the water supply in Yokji-do, and the results were verified.